2021
DOI: 10.3390/coatings11111415
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Solid Lubricants during High Temperature Tribology of Silver-Doped Molybdenum Nitride Coatings Deposited by dcMS and HIPIMS

Abstract: The coating system MoN-Ag is an interesting candidate for industrial applications as a low friction coating at elevated temperatures, due to the formation of lubricous molybdenum oxides and silver molybdates. Film deposition was performed by high-power impulse magnetron sputtering and direct current magnetron sputtering. To facilitate a future transfer to industry Mo-Ag composite targets have been sputtered in Ar/N2 atmosphere. The chemical composition of the deposited MoN-Ag films has been investigated by wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…They found that the optimal addition of Ag (9 at%) shows low friction and improved wear resistance at HT (600 °C ) due to the formation of Ag and AgCrO2 (as seen in Figure 7e). Similarly, various studies have revealed that the optimal concentration of soft/noble metals in primary ceramic hard coatings has a beneficial effect on elevated temperature applications [104][105][106][107]. Similar observations on Cu incorporated into AlTiVN coatings using HIPIMS demonstrated that the friction (0.45) and wear resistance (10−16 m 3 /N⋅m) were significantly enhanced at the optimum Cu concentration of 10.7 at% at high temperature (600 °C ), as reported by Mei et al [99].…”
Section: Figure 6 (A)mentioning
confidence: 99%
“…They found that the optimal addition of Ag (9 at%) shows low friction and improved wear resistance at HT (600 °C ) due to the formation of Ag and AgCrO2 (as seen in Figure 7e). Similarly, various studies have revealed that the optimal concentration of soft/noble metals in primary ceramic hard coatings has a beneficial effect on elevated temperature applications [104][105][106][107]. Similar observations on Cu incorporated into AlTiVN coatings using HIPIMS demonstrated that the friction (0.45) and wear resistance (10−16 m 3 /N⋅m) were significantly enhanced at the optimum Cu concentration of 10.7 at% at high temperature (600 °C ), as reported by Mei et al [99].…”
Section: Figure 6 (A)mentioning
confidence: 99%
“…A second series of substrates was prepared by filling the imprinted voids with a second material; in our case, silver. Silver modified the mechanical properties of the substrate and could, when reacting with the molybdenum nitride film, lead to the formation of lubricant silver molybdates [17]. All of these "smart substrates" were subsequently coated with thin MoN films.…”
Section: Preparationmentioning
confidence: 99%
“…In the case of MoC/MoCN multilayers, the COF as well as the wear rate are significantly reduced compared to an uncoated surface [20]. Additional silver in MoN coatings can serve as a source for the formation of a lubricant phase during the tribological load [21,22]. Finally, so-called "Chameleon" coatings can be produced by adding various additives.…”
Section: Introductionmentioning
confidence: 99%